The Politics of Science and Undone Protection in the "Samsung Leukemia" Case. Issue 4 (1st December 2020) - Kim, Jongyoung; Kim, Heeyun; Lim, Jawoon
Abstract: A labor health dispute between a multinational corporation and patient-workers in Korea received enormous attention from 2007 to 2018, when it was finally and successfully resolved. Sick workers of Samsung Semiconductor claimed they were contaminated by toxic chemicals at their workplace that resulted in their sickness, a contested illness known as "Samsung leukemia." In this dispute, the Korean government and Samsung used epistemological studies to deny the workers' claims. The patient-workers politicized the industrial disease, forming a labor health movement that advocated for workers' rights and welfare. In this long disputed process, they developed their own bottom-up science that collected evidence from their factories and connected this evidence with the claims of counter-experts. They made done "undone science, " which investigated the relationship between the unknown disease and the semiconductor industry. But the undone science has been constructed in the context of "undone protection" stemming not only from chemical exposure in factories that weigh profit over safety but also from institutional failures to protect and compensate the loss of workers' lives and health. The successful resolution of the "Samsung leukemia" case depended on a health movement that worked toward getting undone science and undone protection done simultaneously.